The Job Specification As A Moderating Variable On The Effect Of Job Description Variables On Employee Performance - Titin Titin; Evi Sirait; Rieneke Ryke Kalalo; Mulyadi Mulyadi; Harun Samsuddin (UNIVED Press, 2024)
This research is quantitative research with an explanatory approach, namely research that uses a number of previous studies that the researcher mentioned above and of course is related to the main object in this research, namely Job Description, Job Specification and Employee Performance as the main reference. The data that researchers used in this research is primary data that researchers obtained directly from 500 Indomaret employees throughout Indonesia using the method of distributing data through an online questionnaire instrument. The questionnaire that the researcher distributed contained 5 items stating strongly agree, agree, normal/average, disagree, and strongly disagree from 18 question items which the researcher would validate first. The data mentioned by the researcher above was analyzed using the smart PLS 4.0 analysis tool